2018
DOI: 10.1007/s10404-018-2094-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-droplet acoustic particle focusing: simulations and experimental observations

Abstract: The aim of this paper is to study resonance conditions for acoustic particle focusing inside droplets in two-phase microfluidic systems. A bulk acoustic wave microfluidic chip was designed and fabricated for focusing microparticles inside aqueous droplets (plugs) surrounded by a continuous oil phase in a 380-μm-wide channel. The quality of the acoustic particle focusing was investigated by considering the influence of the acoustic properties of the continuous phase in relation to the dispersed phase. To simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…As mentioned earlier for high frequency ultrasound, standing waves are often formed in microchannels as the corresponding wavelength approaches that of the channel height or width. Particles in a standing wave experience acoustic radiation forces that move particles either to the pressure node or antinode, known as acoustophoresis, see Figure 1a [46][47][48][78][79][80]. Particle movement is influenced by the acoustic contrast factor [53,[80][81][82][83], which is a function of fluid and particle density, compressibility and the speed of sound in the mixture.…”
Section: Standing Acoustic Waves In Microchannels: Acoustophoretic Force and Streamingmentioning
confidence: 99%
“…As mentioned earlier for high frequency ultrasound, standing waves are often formed in microchannels as the corresponding wavelength approaches that of the channel height or width. Particles in a standing wave experience acoustic radiation forces that move particles either to the pressure node or antinode, known as acoustophoresis, see Figure 1a [46][47][48][78][79][80]. Particle movement is influenced by the acoustic contrast factor [53,[80][81][82][83], which is a function of fluid and particle density, compressibility and the speed of sound in the mixture.…”
Section: Standing Acoustic Waves In Microchannels: Acoustophoretic Force and Streamingmentioning
confidence: 99%
“…It has previously been shown that to generate a strong and homogeneous standing wave field in two-phase systems, it is important to match the acoustic properties of the continuous phase and the dispersed phase. 35 Here, light mineral oil was used as a continuous phase as it has similar acoustic properties to water.…”
Section: Acoustophoresismentioning
confidence: 99%
“…In the subsequent step on applying 136 MHz acoustic power the 3.2 mm particles remained traveling along the focused stream while the 4.8 m m particles were deflected to the opposite side of the channel, and thus, separated. The two stage TSAW based separation system was also used for separating particles of different sizes confined within a droplet (Park et al, 2017;Fornell et al, 2018b) as shown in Figure 12. In first stage an ultrasonic beam of 135 MHz pushes particles of both sizes (5 and 10 m m) to one side within the droplet then the low frequency (95 MHz) beam effects only the larger particles, thus the positions of both sizes are controlled and eventually a split of the droplet occurs at the Y-junction and the intradroplet separation take place.…”
Section: Sheathless Traveling Surface Acoustic Waves Particle Separation Techniquesmentioning
confidence: 99%